FAKTOR GENETIK TERHADAP KEJADIAN PREEKLAMPSI DI RSD IDAMAN BANJARBARU - Januarsih Januarsih; Ahmad Rizani (Jurnal Inovasi Penelitian, 2022)
Preeclampsy occurs in 5% - 8% of pregnancies, leading to high morbidity and mortality in both mother and fetus. In RSD Idaman Banjarbaru, the incidence of Preeclampsy increases every year. In 2014 there were 265 (4.4%) of the 5961 deliveries and increased in 2017 by 363 (7.6%) from 4776 deliveries. The instrument in this study used secondary data, namely data obtained from the childbirth register book at Idaman Banjarbaru Hospital in 2017 and primary data obtained from filling out a questionnaire given to respondents about maternal determinants with Preeclampsy incidence at RSD Idaman Banjarbaru in 2017. Out of 100 people 6 (6%) of mothers who had PEB had a genetic history of the mother and the rest had no genetic history of their mother. Meanwhile, of the 100 mothers who did not experience PEB, all of them had no maternal genetic history. Based on the results of calculations that have been carried out, the results of hypothesis testing using the Spearman Rank show that there is no significant relationship between genetic factors and the incidence of severe preeclampsia (PEB) as indicated by the value obtained, namely (0.013 <0.05). The amount of correlation that occurs between the two variables is 0.76, which means that the relationship between genetic factors and the incidence of PEB is weak.